Conditional ablation and conditional rescue models for Casq2 elucidate the role of development and of cell-type specific expression of Casq2 in the CPVT2 phenotype. (14th February 2018) - Flores, Daniel J; Duong, ThuyVy; Brandenberger, Luke O; Mitra, Apratim; Shirali, Aditya; Johnson, John C; Springer, Danielle; Noguchi, Audrey; Yu, Zu-Xi; Ebert, Steven N; Ludwig, Andreas; Knollmann, Bjorn C; et al.
Abstract: Cardiac calsequestrin (Casq2) associates with the ryanodine receptor 2 channel in the junctional sarcoplasmic reticulum to regulate Ca 2+ release into the cytoplasm. Patients carrying mutations in CASQ2 display low resting heart rates under basal conditions and stress-induced polymorphic ventricular tachycardia (CPVT). In this study, we generate and characterize novel conditional deletion and conditional rescue mouse models to test the influence of developmental programs on the heart rate and CPVT phenotypes. We also compare the requirements for Casq2 function in the cardiac conduction system (CCS) and in working cardiomyocytes. Our study shows that the CPVT phenotype is dependent upon concurrent loss of Casq2 function in both the CCS and in working cardiomyocytes. Accordingly, restoration of Casq2 in only the CCS prevents CPVT. In addition, occurrence of CPVT is independent of the developmental history of Casq2-deficiency. In contrast, resting heart rate depends upon Casq2 gene activity only in the CCS and upon developmental history. Finally, our data support a model where low basal heart rate is a significant risk factor for CPVT.